Simulation of intracranial hemodynamics by an efficient and accurate immersed boundary scheme. (15th September 2021) - Lampropoulos, Dimitrios S.; Bourantas, George C.; Zwick, Benjamin F.; Kagadis, George C.; Wittek, Adam; Miller, Karol; Loukopoulos, Vassilios C.
Abstract: We use computational fluid dynamics (CFD) to simulate blood flow in intracranial aneurysms (IAs). Despite ongoing improvements in the accuracy and efficiency of body‐fitted CFD solvers, generation of a high quality mesh appears as the bottleneck of the flow simulation and strongly affects the accuracy of the numerical solution. To overcome this drawback, we use an immersed boundary method. The proposed approach solves the incompressible Navier–Stokes equations on a rectangular (box) domain discretized using uniform Cartesian grid using the finite element method. The immersed object is represented by a set of points (Lagrangian points) located on the surface of the object. Grid local refinement is applied using an automated algorithm. We verify and validate the proposed method by comparing our numerical findings with published experimental results and analytical solutions. We demonstrate the applicability of the proposed scheme on patient‐specific blood flow simulations in IAs. Abstract : We use an immersed boundary method to simulate blood flow in intracranial aneurysms (IAs). The proposed approach solves the incompressible Navier–Stokes equations on a rectangular domain discretized using uniform Cartesian grid using the finite element method. The immersed object is represented by a set of Lagrangian points located on the surface of the object. Grid local refinement is applied using an automated algorithm. We demonstrate the applicability of the proposed scheme on patient‐specific blood flow simulations in IAs.